Effects of soil moisture conservation practice, irrigation and fertilization on Jatropha curcas - Phiwngam, Aran; Anusontpornperm, Somchai; Thanachit, Suphicha; Wisawapipat, Worachart (Agriculture and Natural Resources, 2016)
A field experiment was conducted on an Ultic Haplustalf at the Kanchanaburi Research Station, Muang district, Kanchanaburi province, western Thailand between July 2011 and June 2012. Split plots in a randomized complete block design with four replications were employed, having eight main plots (soil moisture conservation practice and irrigation, W1eW8) and 2 sub plots (fertilization, F1 and F2). Jatropha curcas (KUBP 78-9 Var.), having been planted at 2 x 2 m spacing, was aged 2 yr when the experiment was commenced. The highly significantly heaviest 100-seed weight of 42 g was obtained 1 mth after water irrigation which had been applied at the rate of 16 L/plant, particularly in the treatment with crop residue mulching (W8) but there were no significant differences among the other treatments where irrigation had been applied (W5-W7). Fertilization and a combination between different fertilizers and soil moisture conservation schemes plus irrigation showed no different effect on the weight of 100 seeds throughout the year of measurement. Growing J. curcas with drip-irrigated water at the rate of 16 L/plant applied every 2 d and crop residue mulching (W8) significantly gave the highest seed yield of 1301.3 kg/ha at 15% moisture content. There were no significant differences among the seed yields from the plots applied with the same amount of irrigated water but with no mulching (W7) and half that amount of irrigated water with crop residue mulching (W6), producing yields of 1112.0 kg/ha and 1236.3 kg/ha, respectively. Three-year-old J. curcas gave inferior seed yield when grown with no irrigated water supply (W1-W4). The application of 50-150-150 kg/ha of N-P2O5-K2O significantly induced a higher amount of seed yield (933.9 kg/ha) than did the addition of 93.75-93.75-93.75 kg/ha of N-P2O5-K2O (786.3 kg/ha). The interaction between soil moisture conservation plus irrigation and fertilizer was clear. Applying 50-150-150 kg/ha of N-P2O5-K2O together with water irrigation at the rate of 16 L/plant (W7F2) significantly promoted the greatest seed yield of 1415.2 kg/ha. However, irrigated water can be reduced to 8 L/plant in combination with crop residue mulching and the addition of 50-150-150 kg/ha of N-P2O5-K2O (W6F2) and the plants still performed well, producing a seed yield of 1356.4 kg/ha. In addition, with no irrigation, none of the moisture conservation practices (W2-W4) showed any significant effects regardless of the different fertilizers applied.